Solid-phase microextraction-based cuticular hydrocarbon profiling for intraspecific delimitation in Acyrthosiphon pisum. - Nan Chen; Yu Bai; Yong-Liang Fan; Tong-Xian Liu (PLoS ONE, 2017)
Insect cuticular hydrocarbons (CHCs) play critical roles in reducing water loss and chemical communication. Species-specific CHC profiles have been used increasingly as an excellent character for species classification. However, considerably less is known about their potential for population delimitation within species. The aims of this study were to develop a solid-phase microextraction (SPME)-based CHC collection method and to investigate whether CHC profiles could serve as potential chemotaxonomic tools for intraspecific delimitation in Acyrthosiphon pisum. Optimization of fibers for SPME sampling revealed that 7 μm polydimethylsiloxane (PDMS) demonstrated the most efficient adsorption of CHCs among five different tested fibers. SPME sampling showed good reproducibility with repeated collections of CHCs from a single aphid. Validation of SPME was performed by comparing CHC profiles with those from conventional hexane extractions. The two methods showed no qualitative differences in CHCs, although SPME appeared to extract relatively fewer short-chained CHCs. While CHC profiles of a given population differed among developmental stages, wing dimorphism types, and host plants, wingless adult aphids showed very low variance in relative proportions of individual CHC components. Reproducibility of CHC profiles was explored further to classify wingless adult morphs of A. pisum from five different geographic regions that showed no variation in mitochondrial COI gene sequences. Our results demonstrate that CHC profiles are useful in intraspecific delimitation in the field of insect chemotaxonomy.